EFFECTS OF NICKEL CHLORIDE ON HEMATOLOGICAL AND DEVELOPMENTAL PARAMETERS IN Wistar albino PREGNANT RATS - Ounassa Adjroud; MOUFFOK, S (Ass. Univ. Bull. Environ. Res, 2009)
Several reports have suggested that soluble salts nickel may affect on hematopoiesis and development. In this study female Wistar albino rats (180-300g) received NiCl2, 6H2 O, subcutaneously (25, 50 and 100 mg/kg body weight (b w) or in drinking water (20 mg/100 ml). Selenium (0.3 mg/kg b w, s.c.) was combined to NiCl2 (100 mg/kg b w, s.c.). Control groups received NaCl 0.9% (0.3 ml s.c) or drinking distilled water. All groups of rats were injected on day 4 of pregnancy in pre-implantation period. Haematological parameters were recorded on day 6 and 21 of pregnancy. Developmental parameters were assessed on day 21 of pregnancy. 25 mg/kg b w, of NiCl2 s.c, induced on day 6 an immediate and significant decrease in erythrocyte counts, hematocrit values, and haemoglobin concentrations. This depletion was maintained on day 21 of pregnancy compared to control values.On other hand 50 mg/k b w, NiCl2, s.c, reduced on day 6 of pregnancy the erythrocyte counts, hematocrit values and platelets counts. Inversely, on day 21 this dose elevated the erythrocyte counts, hematocrit values and haemoglobin concentrations ,with depletion of the platelets counts compared to control values. In group introduced 100 mg/kg b w, of NiCl2, s.c had no effect on all haematological parameters studied. NiCl2, significantly reduced the maternal body weight on day 6 and 21 of pregnancy in a dose – dependent manner in rats treated subcutaneously and in drinking water compared with control values. NiCl2, s.c. (100 mg/kg b w) markedly reduced the number of live fetuses and elevated the number of abortions on day 21 of pregnancy compared to control values. NiCl2, s.c or in drinking water had no effect on fetal body weight. Selenium (0.3 mg/kg b w, s.c.) combined to NiCl2 (100 mg/kg b w, s.c.) did not improve the effect of NiCl2.